Jejunal Diverticular Perforation Causing Small Bowel Obstruction in a Type 4 Hiatal Hernia: A Rare Case Report of a Nonagenarian Patient and Review of Relevant Literature - Saptarshi Biswas; Shekhar Gogna; Prem Patel (Case Reports in Surgery)
Type IV paraesophageal hernia (PEH) is very rare and is characterized by the intrathoracic herniation of the abdominal viscera other than the stomach into the chest. We describe a case of a 90-year-old male patient who presented at our emergency department complaining of epigastric pain that he had experienced over the past few hours and getting progressively worse. On the day after admission, his pain became severe. Chest radiography revealed an intrathoracic intestinal gas bubble; emergency exploratory laparotomy identified a type IV PEH with herniation of only the jejunum with perforated diverticula on mesenteric side through a hiatal defect into mediastinum. There are a few published cases of small bowel herniation into the thoracic cavity in the literature. Our patient represents a rare case of an individual diagnosed with type IV PEH with herniation of jejunum with perforated diverticula.